GE_GERICHTE P/16511/2023 vom 13. August 2025 - GE Cour de justice (2025)
CLASSEMENT DE LA PROCÉDURE;PLAINTE PÉNALE;FRAIS(EN GÉNÉRAL);ASSISTANCE JUDICIAIRE;DÉPENS;RETRAIT(VOIE DE DROIT) | CPP.319.al1.letd; CPP.426; CPP.135; CC.28